Dent damage identification in stiffened cylindrical structures using inverse Finite Element Method. (15th February 2020) - Li, Mingyang; Kefal, Adnan; Cerik, Burak Can; Oterkus, Erkan
Abstract: The offshore industry has been using stiffened thin-walled steel cylindrical structures for decades, particularly as the columns of floating offshore installations. The floating offshore installations may be subjected to severe marine environmental conditions. Accidents such as collisions may also occur. Structural Health Monitoring (SHM) is a viable tool to maintain safe operation of offshore installations. Inverse Finite Element Method (iFEM) is one of the most powerful methods for SHM process. Hence, this study focuses on the application of iFEM methodology to thin-walled cylindrical structures representing the columns of floating offshore installations. iFEM methodology is verified by comparing its displacement results against reference finite element method (FEM) solution. After this verification, four different damage cases with different size, location and number of damages are considered. By using a newly introduced damage parameter and von Mises strain distribution iFEM accurately identified the correct damage locations and sizes. Therefore, it is concluded that iFEM can be used for structural damage prediction in offshore structures with high accuracy even if the number of the strain sensors is limited. Highlights: Inverse Finite Element Method is used for damage identification. Stiffened cylindrical structures are investigated. A new damage parameter is introduced for damage identification. Damage cases with different sizes, locations and numbers are considered.